Relevance of the Theory of Relevance: Beyond Classical Approaches to Translation: Selected Verses of the Holy Qur'an as a case study - Fayed, Atef S. (2014)
A Master of Arts thesis in Translation and Interpreting MATI (English/Arabic/English) by Atef S. Fayed entitled, "Relevance of the Theory of Relevance: Beyond Classical Approaches to Translation: Selected Verses of the Holy Qur'an as a case Study," submitted in May 2014. Thesis advisor is Dr. Ahmed Ali. Soft and hard copy available.